1975
DOI: 10.1128/jb.122.1.99-105.1975
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of extrachromosomal deoxyribonucleic acid for exfoliative toxin production from phage group II Staphylococcus aureus

Abstract: The ability of phage group II staphylococcal strain UT 0101 to produce exfoliative toxin and bacteriocin could be eliminated at a high frequency after growth at high temperatures or in the presence of ethidium bromide or sodium dodecyl sulfate. Extrachromosomal deoxyribonucleic acid, associated with the genes for exfoliative toxin and bacteriocin production, was isolated from strain UT 0101 but was absent from an ethidium bromide-cured substrain. The molecular weight of the exfoliative toxin plasmid, determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
0

Year Published

1977
1977
1991
1991

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 16 publications
(20 reference statements)
3
37
0
Order By: Relevance
“…Rogolsky and his co-workers in a series of studies have attempted to define the genetic basis of ET production in S. aureus (Rogolsky et al, , 1976Warren et al, 1974Warren et al, , 1975Wiley 8z Rogolsky, 1977). In early studies no evidence was obtained for linkage of ET determinants to lysogenic phages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rogolsky and his co-workers in a series of studies have attempted to define the genetic basis of ET production in S. aureus (Rogolsky et al, , 1976Warren et al, 1974Warren et al, , 1975Wiley 8z Rogolsky, 1977). In early studies no evidence was obtained for linkage of ET determinants to lysogenic phages.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases the loss of ET coincided with the loss of bacteriocin production which suggested that the two determinants might be carried on the same plasmid . Finally, a plasmid of '56s' in the covalently closed circular form was identified by sucrose density gradient centrifugation and was correlated with the ET and bacteriocin markers (Warren et al, 1975).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies made in this laboratory have revealed that certain phage group 2 staphylococcal strains harbor an unstable 56S virulence plasmid with a molecular weight of approximately 3 x 107 (18,19,24). The covalently closed circular structure of this large plasmid spontaneously converts to the open circular form, and this conversion is enhanced in the presence of either sodium dodecyl sulfate, Pronase, or ethidium bromide (19,24).…”
mentioning
confidence: 99%
“…The genetic information controlling enterotoxin production in Escherichia coli is located on transmissible plasmids (Smith & Gyles 1970;Gyles et al 1974) and in certain strains of Staph. aureus production of epidermolytic toxin is plasmid controlled (Warren et al 1975). The advanced state of development of E. coli plasmid genetics has naturally facilitated elucidation of genetic control of E. coli enterotoxin production.…”
Section: Approaches To the Study Of Toxin Actionmentioning
confidence: 99%